2017
DOI: 10.1111/epi.13688
|View full text |Cite
|
Sign up to set email alerts
|

Toll‐like receptor 3 deficiency decreases epileptogenesis in a pilocarpine model of SE‐induced epilepsy in mice

Abstract: This study reveals novel insights into the pathophysiology of epilepsy and the contribution of TLR3 to disease progression. Our results identify the TLR3 pathway as a potential future therapeutic target in SE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 43 publications
(95 reference statements)
0
28
0
Order By: Relevance
“…wild‐type mice, in the absence of changes in SE severity or duration, supporting the involvement of this receptor in epileptogenesis . Recently, the contribution of TLR3 to disease progression has been reported in a mouse model of SE‐induced epilepsy .…”
Section: Il‐1r/toll‐like Receptor Signallingmentioning
confidence: 76%
“…wild‐type mice, in the absence of changes in SE severity or duration, supporting the involvement of this receptor in epileptogenesis . Recently, the contribution of TLR3 to disease progression has been reported in a mouse model of SE‐induced epilepsy .…”
Section: Il‐1r/toll‐like Receptor Signallingmentioning
confidence: 76%
“…In children with genetic defects that shared the common feature of encoding proteins involved in TLR3 interferon signaling pathways, mutations in TLR3 were associated with recurrent HSE (Zhang et al, 2007;Lim et al, 2014;Steiner and Tyler, 2014). Whether the defect in the TLR3 receptor reduces inflammation-mediated epileptogenesis as shown in animal models needs to be established in future clinical studies (Benninger et al, 2014;Gross et al, 2017). Regarding autoimmune-mediated encephalitis, reports suggest that the most commonly recognized cause of antibody-mediated autoimmune encephalitis, anti-N-methyl-D-aspartate receptor encephalitis, may in some cases be triggered by and follow HSE (Armangue et al, 2013(Armangue et al, , 2015.…”
Section: Prognosismentioning
confidence: 99%
“…Numerous studies have implicated inflammatory and immune response signaling in seizure onset and epileptogenesis. [1][2][3][4][5][6][7][8][9][10][11][12][13] These studies suggest that neuroinflammation is both an outcome and a contributor to seizures, and sustained neuroinflammation may play a role in the development of epilepsy. An earlier review of the relationship between inflammation and epilepsy concluded that "brain inflammation is not a mere hallmark of tissue pathology but plays an active role in sustaining or precipitating seizures."…”
Section: Introductionmentioning
confidence: 94%
“…14 The central role of proinflammatory cytokines in initiating and sustaining seizures is suggested by three main observations drawn from clinical and animal studies: (1) molecular analysis of epileptogenic human tissue often reveals elevation of pro-inflamma-tory cytokines; (2) animal studies show that induced seizures produce an inflammatory cascade mediated by cytokines; and (3) animal studies demonstrate that induction of key cytokines results in increased seizure susceptibility. Collectively, these observations form the basis of the "vicious cycle" characterization of epilepsy, 12,[15][16][17] and proinflammatory cytokines are key effectors of the cycle. These neuroinflammatory mediators have become attractive targets for the development of new therapeutic approaches for the treatment of intractable epilepsy.…”
Section: Introductionmentioning
confidence: 98%